Linguistic challenges lived by university students in Bogotá in the development of academic literacy - Nanwani, Sanjay (Colombian Applied Linguistics Journal, 2009)
The focus of this paper is on the challenges that Colombian university students live when developing academic writing in English as a foreign language. At the macro level, it points to the importance of a theoretically informed understanding of teaching practices in ELT; at the micro level it intends to sensitize ELT practitioners, and particularly academic writing instructors, on the diverse challenges students – particularly non-native learners – experience when appropriating a largely unknown discourse upon entry to the university. Excerpts from participants in a two-year study intertwine with a theoretical discussion on academic writing are presented.